Answer:
The equivalent expression to the given expression is
[tex]\frac{\frac{3x}{x+1}}{x+1}=\frac{3x}{(x+1)^2}[/tex]
Step-by-step explanation:
Given expression is [tex]\frac{\frac{3x}{x+1}}{x+1}}[/tex]
To find the equivalent expression to the given expression as below :
[tex]\frac{\frac{3x}{x+1}}{x+1}}[/tex]
Rewritting the above given expression as below :
[tex]\frac{\frac{3x}{x+1}}{x+1}=\frac{\frac{3x}{x+1}}{\frac{x+1}{1}}[/tex]
[tex]=\frac{3x}{x+1}\times\frac{1}{x+1}}[/tex] (by using the fractional property )
[tex]\frac{\frac{3x}{x+1}}{x+1}=\frac{3x}{(x+1)^2}[/tex]
Therefore [tex]\frac{\frac{3x}{x+1}}{x+1}=\frac{3x}{(x+1)^2}[/tex]
Therefore the equivalent expression to the given expression is
[tex]\frac{\frac{3x}{x+1}}{x+1}=\frac{3x}{(x+1)^2}[/tex]